Evaluation of Banana Plant Waste and its Silage Based Diet on Performance of Osmanabadi Goats - Anjaneya, S. N.; Ramachandra, B.; Thirumalesh, T.; Anup Kumar, P. K. (Indian Journal of Animal Nutrition, 2019)
The fresh banana plant waste and its silage based diets were evaluated in Osmanabadi goats for six weeks. Thirty goats (n=30) were divided into six groups of five each and allotted to one of the following diets: T1 (Banana plant waste plus concentrate feed mixture), T2(silage alone), T3(silage Â plus concentrate feed mixture), T4 (silage plus soybean meal), T5 (silage plus maize mixed with slow releasing nitrogen product) and T6(silage plus wheat bran). Restricted feeding of red gram strawÂ was carried out in all groups. The crude protein content of the diets varied from 6.18 to 19.80%.The total dry matter (TDM) and crude protein (CP) intake for T1, T2, T3, T4, T5and T6 groups varied from 384.75 to 554.07 and 23.79 to 95.57 g/d respectively. Furthermore, animals in all the groups were on positive nitrogen balance with similar biochemical parameters. It was concluded that, banana plant with concentrate feed mixture and silage with soybean meal based diets were superior over remaining silage based diet in terms of achieving higher body weight gain.